The transformation of Muslim mystical thought in the Ottoman empire: the rise of the Halveti order, 1350 - 1650 - Curry, John J. (Edinburgh Univ. Press, 2010)
"One of more poorly understood aspects of the Ottoman Empire has been the flourishing of Sufi mysticism under its auspices. This study tracks the evolution of the Halvetî order from its modest origins in medieval Azerbaijan to the emergence of the influential Sabaniyye, whose range once extended throughout the Empire. By carefully reconstructing the lives of formerly obscure figures in the history of the order, a complex picture emerges of the connections among Halvetî groups, the state, and society. Even more important, since the Sa'baniyye grew out of the towns and villages of the northern Anatolian mountains rather than the major urban centres, this work brings a unique perspective to the lives, work, and worship of Ottoman subjects outside of the major urban centres of the Empire. Along the way, the study sheds light on less-visible actors, such as women and artisans, and challenges generalizations about the activities and strategies of Ottoman mystics." -- Book jacket